The Scholarship of Teaching and Learning in Religious Studies - Gravett, Emily O. (Journal of the American Academy of Religion, 2016)
In 2014, a roundtable on pedagogy appeared in the Journal of the American Academy of Religion with an initial piece by Vanessa Sasson. Although neither Sasson nor the respondents explicitly situated her article as a part of the broader body of work known as the “Scholarship of Teaching and Learning” (SoTL), readers would reap benefit from such a contextualization. In this article, after first exploring what SoTL is and how it has interacted with the field of religious studies, I explore three main elements of this particular kind of scholarship: research with human subjects and the Institutional Review Board, a foundation in other scholarship, and assessment. In these three areas, I uncover special questions, considerations, and resources for all religious studies instructors interested in embarking upon a SoTL project with the aim of contributing to the ongoing conversation about pedagogy.